Limites e diretrizes para formação, interpretação e aplicação dos julgados paradigmáticos - Mohrer, Michelle Ris (2022)
This study aims to analyze the paradigmatic cases in Brazilian Law, highlighting their indispensability regarding the implementation of constitutional principles, in particular legality, legal certainty and equality, since observed the limits and guidelines imposed by the Federal Constitution and objectified by the New Code of Civil Procedure for their generation, interpretation and application